Simple acoustic metagrating for perfect two- and three-beam splitting - Song, Ailing; Sun, Chaoyu; Xiang, Yanxun; Xuan, Fu-Zhen (Frontiers in Materials, 2023)
Acoustic metasurfaces have been widely explored and attracted great attention for their extraordinary wavefront manipulation abilities. In this paper, we propose a simple acoustic metagrating with periodic grooves that can split a normally incident beam into two or three reflected beams. The amplitudes and power flows of different reflected beams can be manipulated by changing the groove parameters. The mirror reflected wave is suppressed for equal two-beam splitting case and allowed for three-beam splitting case. Theoretical analysis and numerical simulations are performed to demonstrate the perfect two- and three-beam splitting performances based on local power conservation. Our research work provides a simple method for designing acoustic beam splitters and has extensive applications in acoustic sensing and communication.